Reconceiving Reproductive Health Theological and Christian Ethical Reflections - Bowers du Toit, Nadine (Reformed Theology in Africa Series, 2019)
While reproduction is fairly often touched upon in theological and Christian ethical discussions, reproductive health is not. However, reproductive health is a matter of theological and ethical concern. Discussion pertaining to reproductive health includes a number of debates about, for instance, abortion and the termination of pregnancy, reproductive loss, childlessness, infertility, stillbirth, miscarriage and adoption. Additionally, new reproductive possibilities made available by the development of reproductive technology have necessitated theological and ethical reflection on, for example, surrogacy, post-menopausal pregnancies, litter births, single mothers or fathers by choice, in vitro fertilisation and the so-called saviour siblings. These new developments compel us to reconceive our notions of what reproductive health is or should be. Many of these topics are receiving increasing attention in a variety of theological publications. The focus of this volume is unique, however, and to the best of our knowledge, this is the first volume dealing not only with reproductive issues, but also reflecting theologically and ethically on reproductive health. It makes a contribution by providing a variety of perspectives from different theological fields on this theme, and in many chapters, focussing especially on the South African context. These discussions are also part of urgent debates within churches, which require developing life-giving theological language and imaginative theological alternatives that may speak to experiences of matters relating to reproductive health. The popular books, TV series and films that touch upon these discussions - including The Handmaid's Tale and Mother! - strengthen the perception that a more in-depth theological and ethical discussion on the theme may be necessary, particularly towards exploring stories and confessions from our faith tradition that may provide us with a timely opportunity to do the important work of theological 'reconceiving'.